EDITORIAL - Hayes, Grahame (PINS-Psychology in Society, 2025)
While there is no distinct theme that pulls the articles 1n this edition together, the issues covered do cohere around two broad central problems of concern to psychologists and social scientists in South Africa at the moment. The one set of articles (Natalie Leon and Susan Lea; Tammy Shefer and Beatie Hofmeyr; Henk Eichhorn) raise some important issues related to black students' experiences and social struggles on the predominantly white university campuses in this country. The other set of articles have to do with the restructuring of mental health practices, one in relation to Nicaragua (Vogelman) and the other South Africa (Perkel).